2016
DOI: 10.1093/hmg/ddw187
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing reveals aberrant alternative splicing in Huntington's disease

Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by a CAG expansion in the gene-encoding Huntingtin (HTT). Transcriptome dysregulation is a major feature of HD pathogenesis, as revealed by a large body of work on gene expression profiling of tissues from human HD patients and mouse models. These studies were primarily focused on transcriptional changes affecting steady-state overall gene expression levels using microarray based approaches. A major missing component, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 106 publications
(162 reference statements)
5
119
0
Order By: Relevance
“…These results suggest that established tumors respond to the siCAG/CUG treatment. This was confirmed in another experiment in which 10 6 HeyA8 cells were injected and mice were first treated 3 times a week and then switched to daily treatment 19 days after tumor cell injection (data not shown).…”
Section: Super Toxic Tnr-derived Sirnas Kill Cells By Targeting Tnr Ssupporting
confidence: 52%
See 2 more Smart Citations
“…These results suggest that established tumors respond to the siCAG/CUG treatment. This was confirmed in another experiment in which 10 6 HeyA8 cells were injected and mice were first treated 3 times a week and then switched to daily treatment 19 days after tumor cell injection (data not shown).…”
Section: Super Toxic Tnr-derived Sirnas Kill Cells By Targeting Tnr Ssupporting
confidence: 52%
“…Another mechanism by which CAG/CUG TNRs could be toxic at the RNA level is by interfering with cellular splicing. This has been shown for CUG in DM1 [9] and CAG in HD [10].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Table S5 lists around 200 proteins that changed in abundances in our study and in at least one of the three transcriptomics 44,55,56 or two proteomics studies, 26,27 or have been identified as Htt interactors in one out of two previous Htt interaction studies. 21,57 The most comparable to our work is the gene profiling study by Hodges and coworkers 44 performed on several human brain regions, including cortex.…”
Section: Discussionmentioning
confidence: 95%
“…Out of these 25 genes, we found 11 corresponding proteins that changed concordantly. In addition, the most recent RNA-seq study, performed on comparable human brain region, 56 includes 224 differentially expressed genes in HD versus controls. 56 The common genes between the above and our study are also included in Table S5.…”
Section: Discussionmentioning
confidence: 99%